2017
DOI: 10.1002/jsfa.8337
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive method for the quantification of trans‐linolenic acid isomers in trilinolenin of edible oils using an ionic liquid capillary column

Abstract: The developed method has been successfully applied to the analysis of ALA isomers in heated pure trilinolenin as well as to trilinolenin in various edible oils, and the TALA isomerization pathways in heated trilinolenin were verified. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…As the heating temperature increased, the types and quantities of TALAs also increased. t 9, t 12, c 15‐C18:3 was not observed until the linseed oil was heated for 6 h at 170 °C, which is consistent with the findings of Guo et al (2017), who reported that t 9, t 12, c 15‐C18:3 was the most difficult di‐TALA to generate. The order at 200 °C was consistent with the experimental results of Guo et al (2017).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…As the heating temperature increased, the types and quantities of TALAs also increased. t 9, t 12, c 15‐C18:3 was not observed until the linseed oil was heated for 6 h at 170 °C, which is consistent with the findings of Guo et al (2017), who reported that t 9, t 12, c 15‐C18:3 was the most difficult di‐TALA to generate. The order at 200 °C was consistent with the experimental results of Guo et al (2017).…”
Section: Resultssupporting
confidence: 90%
“…Chen et al (2017) found that a large number of free radicals produced by lipid oxidation can cause the oxidation of oxidation‐resistant fatty acids, such as palmitic acid. Moreover, the further isomerisation of t 9, c 12, c 15‐C18:3 and c 9, t 12, c 15‐C18:3 to t 9, t 12, c 15‐C18:3 could also play a role in reducing their content (Guo et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review has been published by Fanali et al [11], summarizing the application of IL-based columns in GC analyses of FAMEs, and SLB-IL111 was suggested for FAME isomer analyses. This extremely polar column has been used to determine the FA composition in milk fat of different origins [5,12,13], in oils (such as linseed oil [14], menhaden fish oil [15] or various edible oils [16]) and fast food samples [17]. In particular, the SLB-IL111 column was applied to separate cis/trans monounsaturated FAs C14:1 to C20:1 to compare its performance with other commercially available columns, such as the SP-2560 and the CP-Sil 88 ones [6].…”
Section: Introductionmentioning
confidence: 99%